Luminescent crystal and its manufacture

By dispersing the solid materials in liquids and using surfactants and prepolymers, the problems of uneven size distribution and reaction in quantum dot manufacturing are solved, and the stability of high-photoluminescent quantum dots and the feasibility of commercial applications are achieved.

CN114716997BActive Publication Date: 2024-12-13AVANTAMA AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210453488.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-08-11
Filing Date
2017-06-26
Publication Date
2024-12-13
Estimated Expiration
2037-06-26

AI Technical Summary

Technical Problem

The prior art has problems such as uneven size distribution, difficulty in controlling particle growth, non-stoichiometric reactions, numerous by-products, and solvent exchange needs in the manufacturing of quantum dots (QDs), which leads to unattractive commercial applications.

Method used

A method is used to reduce particle size and stabilize by providing solid materials, including organic and metal cations, dispersing in liquids, using surfactants and prepolymers, grinding balls, ultrasonic or high shear mixing, etc. Quantum dots, forming luminescent crystals with narrow size distribution and high photoluminescent quantum.

Benefits of technology

The stability of quantum dots and the improvement of photoluminescent quantum are achieved, and the manufacturing cost is reduced. It is suitable for electronic equipment and decorative coatings, and does not require solvent exchange, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114716997B_ABST
    Figure CN114716997B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of luminescent crystals (LC), and more specifically to formula A 1 a M 2 b X c Quantum dots (QDs) of the invention, wherein the substituents are defined in the specification. The invention provides methods for making such luminescent crystals, in particular by dispersing suitable starting materials in the presence of a liquid and with the aid of grinding balls; compositions comprising luminescent crystals and electronic devices, decorative coatings; and components comprising luminescent crystals.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the Chinese patent application with application number 201780002428.1, application date June 26, 2017, and invention name “Luminescent Crystals and Their Manufacturing”. Technical Field

[0002] The present invention relates to the field of luminescent crystals (LCs), and more particularly to quantum dots (QDs). The present invention provides methods for making such luminescent crystals, compositions comprising luminescent crystals and electronic devices, decorative coatings and components comprising LCs. Background Art

[0003] Light-emitting crystals, in particular quantum dots, are a known class of materials. Such QDs find many applications in industrial and commercial products, including electronic devices, such as light-emitting diodes or displays.

[0004] Protesescu et al. (Nano Lett., 2015, 15, 3692-3696) disclosed a new class of high-quality luminescent quantum dots (QDs). QDs are synthesized with inexpensive chemicals and have very high dimensional accuracy; the size of QDs is controlled by adjusting synthesis parameters such as temperature and reaction time. However, since the method is difficult to control (due to the very fast particle growth kinetics of the material composition) and difficult to scale up, only very small amounts are synthesized. In addition, the reaction is non-stoichiometric, resulting in a large number of by-products. In addition, the reaction can only be carried out in high-boiling solvents such as octadecene (due to the high reaction temperature), and solvent exchange is required if QDs are needed in low-boiling solvents such as toluene for final application. This synthesis route is called "hot injection" and uses standard laboratory equipment. Due to these shortcomings, the method of synthesizing QDs is not commercially attractive, making QDs expensive.

[0005] Aygüler et al. (J. Phys. Chem. C 2015, 119, 12047-12054) discloses a light-emitting electrochemical cell based on hybrid lead halide perovskite nanoparticles. The authors disclose a method for making such nanoparticles of 50-90 nm in size, also realizing that the size distribution is not uniform. The document also points out the difficulties in obtaining these materials, since the dropwise addition of reactants is crucial to obtain pure compounds. Moreover, a capping agent is required to control and limit crystal growth.

[0006] Li et al. (Chem. Mater., 2015, 284-292) describe the formation of (FA, Cs) PbI3 solid alloys in the form of bulk films to stabilize the perovskite structure, where FA represents formamidinium. The materials disclosed in this document do not show luminescence. The formation of the film is obtained by solution in N, N-dimethylformamide. Summary of the invention

[0007] It is therefore an object of the present invention to alleviate at least some of these disadvantages of the prior art. In particular, it is an object of the present invention to provide improved methods of making LC / QDs. Another object is to provide new materials containing LC / QDs suitable for various applications, including electronic devices, optical devices and decorative coatings.

[0008] These objects are achieved by the method defined in claim 1, the ink defined in claim 9, the assembly defined in claim 16 and the device / article defined in claims 17 / 18. Further aspects of the invention are disclosed in the description and the independent claims, and preferred embodiments are disclosed in the description and the dependent claims. The invention provides in particular:

[0009] A method for producing light-emitting crystals, in particular quantum dots (first aspect);

[0010] Compositions in the form of suspensions, also called "inks", or "prepolymer dispersions", and their use (second aspect);

[0011] Solid polymer compositions and uses thereof (third aspect);

[0012] Components (fourth aspect);

[0013] Devices (including electronic devices, optical devices) and articles comprising coated surfaces (fifth aspect);

[0014] A method for producing a polymer composition (sixth aspect);

[0015] A method for manufacturing a component (seventh aspect); and

[0016] · A method for manufacturing a device (eighth aspect).

[0017] The present invention will be described in detail below. It is to be understood that the various embodiments, preferences and ranges provided / disclosed in this specification may be combined arbitrarily. In addition, depending on the specific embodiment, the selected definition, embodiment or range may not be applicable.

[0018] Unless otherwise stated, the following definitions apply to this specification:

[0019] The terms "a", "an", "the" and similar terms used in the context of the present invention are to be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. In addition, the terms "containing", "including" and "comprising" are used herein in their open, non-limiting sense. The term "comprising" shall include both "including" and "consisting of".

[0020] Percentages are given as weight % unless otherwise indicated herein or clearly contradicted by context.

[0021] The term "luminescent crystals" (LC) is known in the art and refers to crystals of 3-500 nm made of semiconductor materials. The term includes quantum dots, typically in the range of 3-15 nm and nanocrystals, typically in the range of greater than 15 nm and up to 100 nm (preferably up to 50 nm) and crystals, typically in the range of greater than 100 nm and up to 500 nm. Preferably, the luminescent crystals are approximately equiaxed (e.g. spherical or cubic). In the case where the aspect ratio (longest: shortest direction) of all 3 orthogonal dimensions is 1-2, the particles are considered to be approximately equiaxed. Therefore, the LC component preferably contains 50-100% (n / n), preferably 66-100% (n / n), more preferably 75-100% (n / n) equiaxed nanocrystals.

[0022] As the term indicates, LC means luminescence. In the context of the present invention, the term luminescent crystal includes single crystals or can be polycrystalline particles. In the latter case, one particle can consist of several crystal domains (grains) connected by crystalline or amorphous phase interfaces. Due to the presence of surfactants, the luminescent crystals are spatially separated from other particles. Luminescent crystals are semiconductor materials that exhibit a direct band gap (usually in the range of 1.1-3.8 eV, more usually 1.4-3.5 eV, and even more usually 1.7-3.2 eV). When irradiated with electromagnetic radiation equal to or above the band gap, valence band electrons are excited to the conduction band, leaving electron holes in the valence band. The excitons (electron-electron hole pairs) formed then radiatively recombine in the form of photoluminescence, with the maximum intensity concentrated near the LC band gap value and exhibiting a photoluminescence quantum yield of at least 1%. LCs can exhibit electroluminescence when in contact with an external source of electrons and electron holes. In the context of the present invention, LCs do not exhibit mechanoluminescence (e.g., piezoluminescence), chemiluminescence, electrochemiluminescence or thermoluminescence.

[0023] The term "quantum dot" (QD) is known and particularly relates to semiconductor nanocrystals having a diameter typically between 3-15 nm. Within this range, the physical diameter of the QD is smaller than the bulk excitation Bohr radius, resulting in a dominance of quantum confinement effects. As a result, the electronic state of the QD and therefore the band gap is a function of the QD composition and physical size, i.e. the color of absorption / emission is related to the QD size. The optical quality of a QD sample is directly related to its uniformity (more monodisperse quantum dots will have a smaller emission FWHM). When the QD reaches a size greater than the Bohr radius, the quantum confinement effect is hindered and the sample may no longer emit light, because the non-radiative path of the exciton recombination may become dominant. Therefore, QDs are a specific subset of nanocrystals, defined in particular by their size and size distribution. The properties of QDs are directly related to these parameters, distinguishing them from nanocrystals.

[0024] The term "solvent" is known in the art and particularly includes aliphatic hydrocarbons, aromatic hydrocarbons, ethers (including glycol-ethers), esters, alcohols, ketones, amines, amides, sulfones, phosphines, alkyl carbonates. The above organic substances may be substituted or unsubstituted by one or more substituents, for example by halogen (such as fluorine), hydroxyl, C1-4 alkoxy (such as methoxy or ethoxy) and alkyl (such as methyl, ethyl, isopropyl). The above organic substances include straight chain, branched and cyclic derivatives. Unsaturated bonds may also be present in the molecule. The above compounds usually have 4-24 carbon atoms, preferably 5-12 carbon atoms, and most preferably 6-10 carbon atoms.

[0025] The terms "surfactant", "ligand", "dispersant" and "dispersing agent" are known in the art and have essentially the same meaning. In the context of the present invention, these terms refer to an organic substance other than a solvent, used in a suspension or colloid to improve the separation of particles and prevent agglomeration or sedimentation. Without being bound by theory, it is believed that the surfactant physically or chemically attaches to the surface of the particles before or after the particles are added to the solvent, and thereby provides the desired effect. The term surfactant includes polymeric materials and small molecules; surfactants generally include a polar functional end group and a non-polar end group. In the context of the present invention, solvents (e.g., toluene) are not considered surfactants.

[0026] The term "suspension" is known and relates to a heterogeneous fluid of an internal phase (ip, solid) and an external phase (ep, liquid). The external phase comprises one or more dispersants / surfactants, optionally one or more solvents and optionally one or more prepolymers.

[0027] The term "polymer" is known and includes both organic and inorganic synthetic materials. The term "prepolymer" shall include both monomers and oligomers.

[0028] The term "solution processing" is known in the art and means applying a coating or film to a substrate by using solution (= liquid) based starting materials. In the context of the present invention, solution processing relates to the manufacture of commercial products, such as electronic devices, optical devices and articles comprising (decorative) coatings, and also to the manufacture of components / intermediates comprising QD complexes or QD layers. Typically, the application of one or more suspensions is carried out under ambient conditions.

[0029] The term "QD composite" refers to a solid inorganic / organic composite material comprising LC / QDs, a surfactant, and a matrix. The forms of QD composites include thin films, fibers, and bulk materials. QD composites are used in applications where the LC / QDs have only optical functionality, since the LC / QDs are not electronically addressed.

[0030] In a QD composite, the LC / QDs are embedded in a matrix such as a polymer matrix or an inorganic matrix, thereby spatially separating the LC / QDs from each other. The thickness of the QD composite film can vary in a wide range, but is typically 1-1000 microns, depending on the application.

[0031] The term "QD layer" refers to a thin layer comprising light-emitting crystals (particularly QDs) and a surfactant, and contains no or substantially no additional components such as a matrix / binder. The QD layer can find various applications, including quantum dot light-emitting diodes (QLEDs) or quantum dot solar cells. In these applications, the LC / QDs are electronically addressed; current flows through the QD layer by applying a voltage. Depending on the application, the thickness of the QD layer can vary over a wide range, but is typically 3-200nm, preferably 5-100nm, and most preferably 6-30nm. The QD layer can consist of a single layer of LC / QDs and therefore has a thickness equal to the size of the LC / QDs used, thereby defining a lower limit to the thickness.

[0032] Embodiments of the present invention include:

[0033] 1) A method for producing luminescent crystals with a size of 3-500 nm;

[0034] The luminescent crystal is selected from the compound of formula (I)

[0035] [M 1 A 1 ] a M 2 b X c (I) where:

[0036] A 1 represents one or more organic cations selected from ammonium, formamidinium, guanidinium, imidazolium, pyridinium, pyrrolidinium, protonated thiourea,

[0037] M1 represents one or more alkaline metals selected from Cs, Rb, K, Na, Li,

[0038] M 2 represents one or more metals selected from Ge, Sn, Pb, Sb and Bi,

[0039] X represents one or more anions selected from chloride, bromide, iodide, cyanide, thiocyanate, isothiocyanate and sulfide,

[0040] a means 1-4,

[0041] b means 1-2,

[0042] c means 3-9;

[0043] The method comprises the following steps:

[0044] (a) providing a solid material, wherein the solid material (i) has a mole (A 1 +M 1 ), b mole M 2 and c moles of X and (ii) having an average particle size of at least 100 nm and a polydisperse size distribution of typically 50 nm to 100 μm;

[0045] (b) dispersing the material in the presence of a liquid,

[0046] wherein the liquid is selected from the group consisting of (i) a liquid surfactant, (ii) a combination of a surfactant and a solvent, (iii) a combination of a surfactant, a solvent and a prepolymer or a polymer and (iv) a combination of a surfactant and a liquid prepolymer; and

[0047] The dispersion is carried out by stirring with mill balls, by ultrasound, by high shear mixing or by high pressure dispersion.

[0048] 2) The method according to embodiment 1, wherein the dispersing in step (b) is performed by stirring grinding balls.

[0049] 3) The method according to embodiment 1 or 2, wherein the dispersion of step (b)

[0050] by agitator milling with balls having a ball size between 10–1000 μm; and / or

[0051] is performed using a specific power input / weight of suspension of at least 10 W / kg; and / or

[0052] Carry out at a temperature below 120°C.

[0053] 4) A method according to any one of the preceding embodiments, wherein the luminescent crystal is selected from FA1Pb1X3; wherein FA represents formamidinium and X is as defined in Embodiment 1.

[0054] 5) The method according to any one of the preceding embodiments,

[0055] wherein the solvent is selected from aliphatic hydrocarbons (including linear, branched and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol-ethers), esters, alcohols, ketones; and / or

[0056] wherein the surfactant is selected from nonionic, anionic, cationic and zwitterionic surfactants; and / or

[0057] wherein the prepolymer is selected from acrylates, carbonates, sulfones, epoxies, vinyl compounds, polyurethanes, imides, esters, furans, melamines, styrenes, and silicones, in particular acrylates, polyurethanes, styrenes, and silicones; and / or

[0058] The polymer is selected from acrylate polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, polyurethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers and silicone polymers and cyclic olefin copolymers.

[0059] 6) The method according to any one of the preceding embodiments, wherein in step (a) the solid material:

[0060] · obtained by dry synthesis; or

[0061] · obtained by a wet synthesis method; or

[0062] • Formed in situ by stoichiometric reaction of two or more precursors of net stoichiometric composition according to formula (I).

[0063] 7) A method according to embodiment 6, wherein:

[0064] The dry synthesis method is a dry grinding method;

[0065] The wet synthesis method is a precipitation method from a solvent or an aqueous phase;

[0066] - The in situ formation occurs when the starting material is ball milled in the presence of a surfactant and optionally a solvent and / or a liquid prepolymer and / or a dissolved solid polymer.

[0067] 8) A method according to any one of the preceding embodiments, wherein

[0068] The weight ratio of solid material: liquid material (solvent + surfactant + prepolymer + polymer) is 0.0001-0.5; and / or

[0069] The weight ratio of surfactant: solid material is 100–0.01.

[0070] 9) The method according to any one of the preceding embodiments further comprises

[0071] A step of replacing one or more atoms X of the synthesized luminescent crystal (I) with another atom X by anion exchange; and / or

[0072] A step of combining two or more types of luminescent crystals of formula (I).

[0073] 10) A composition in the form of a suspension comprising

[0074] (i) luminescent crystals of formula (I) with a size of 3-500 nm as defined in any one of Embodiments 1 or 3; and

[0075] (ii) a surfactant selected from the group consisting of nonionic, anionic, cationic, and zwitterionic surfactants, but excluding octylammonium bromide and oleic acid; and

[0076] (iii) an optional solvent, preferably selected from aliphatic hydrocarbons (including linear, branched and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol-ethers), esters, alcohols, ketones;

[0077] (iv) optional polymers and / or prepolymers, preferably selected from acrylates, epoxies, polyurethanes, styrenes, silicones and cycloolefin copolymers.

[0078] 11) A composition according to embodiment 10, wherein

[0079] The weight ratio of luminescent crystal (i): liquid material (ii) + (iii) + (iv) is 0.0001-0.5; and / or

[0080] The weight ratio of surfactant (ii):luminescent crystal (i) is 100-0.01, preferably 3-0.02; and / or

[0081] · wherein the polymer or prepolymer concentration is 0.1-30 wt % of the total composition.

[0082] 12) A composition according to any one of embodiments 10-11, wherein the surfactant:

[0083] selected from anionic, cationic, nonionic and zwitterionic surfactants; and

[0084] • comprising a non-polar terminal group selected from an alkyl or alkyl ether chain having 4 to 30 carbon atoms.

[0085] 13) A composition according to any one of embodiments 10-12,

[0086] The composition contains no or substantially no solvent (iii), and

[0087] The weight ratio of LC / QD (i): liquid material (prepolymer (iv) + surfactant (ii)) is preferably 0.0001-0.2.

[0088] 14) A composition according to any one of embodiments 10-13,

[0089] wherein the surfactant (ii) is a liquid surfactant and the composition is free of solvent (iii) and prepolymer (iv), and

[0090] wherein the weight ratio of surfactant (ii):LC / QD (i) is 100–0.01.

[0091] 15) A composition according to any one of embodiments 10-14, wherein

[0092] The luminescent crystal (i) is selected from FA1Pb1X3, wherein FA represents formamidinium and X is defined in Embodiment 1;

[0093] The surfactant (ii) is selected from zwitterionic surfactants; and

[0094] The prepolymer / polymer (iv) is selected from acrylates.

[0095] 16) A solid polymer composition comprising:

[0096] (i) a luminescent crystal of formula (I) having a size of 3-500 nm as defined in any one of embodiments 1 or 3, and

[0097] (ii) a surfactant selected from the group consisting of nonionic, anionic, cationic and zwitterionic surfactants;

[0098] (iii) a hardened / cured polymer, preferably selected from the group consisting of acrylate polymers, epoxy polymers, polyurethane polymers, styrene polymers, silicone polymers and cycloolefin copolymers.

[0099] 17) A solid polymer composition according to embodiment 16, wherein:

[0100] LC / QD:matrix (polymer + surfactant) weight ratio of 0.00001-0.2; and / or

[0101] The weight ratio of surfactant:LC / QD is 100-0.01.

[0102] 18) A solid polymer composition according to any one of embodiments 16-17, wherein

[0103] The luminescent crystal (i) is selected from FA1Pb1X3, wherein FA represents formamidine and X is defined in Embodiment 1;

[0104] The surfactant (ii) is selected from zwitterionic surfactants; and

[0105] The polymer (iv) is selected from acrylates.

[0106] 19) An assembly comprising a sheet-like substrate coated with one or more layers, wherein at least one of the layers is a functional layer, wherein the functional layer comprises a solid polymer composition according to any one of embodiments 16-18.

[0107] 20) A device selected from electronic devices and optical devices, preferably selected from displays (such as LCDs), mobile devices, light-emitting devices (such as QLEDs), and solar cells, wherein

[0108] The device comprises a substrate and a functional layer; and

[0109] The functional layer comprises a solid polymer composition according to any one of embodiments 16-18.

[0110] 21) Articles, especially decorative coatings, wherein

[0111] The article comprises a substrate and a coating,

[0112] The coating comprises a solid polymer composition according to any one of embodiments 16-18.

[0113] 22) Use of the composition according to any one of embodiments 10-15 for manufacturing

[0114] An assembly according to embodiment 19; or

[0115] The apparatus according to embodiment 20; or

[0116] • The article according to embodiment 21.

[0117] 23) Use of the composition according to any one of embodiments 16-18 for converting blue light into white light, especially in QLED or in LCD. BRIEF DESCRIPTION OF THE DRAWINGS

[0118] The invention may be better understood with reference to the accompanying drawings.

[0119] Figures 1(a) and (b) summarize various aspects of the present invention. Figure 1b In the figure, the x-axis represents particle size / nm and the y-axis represents number of particles / arbitrary unit. On the left is the starting material (bulk material) provided in step (a), and on the right is the LC / QD of the present invention obtained in step (b) of the present invention.

[0120] Figure 2 X-ray diffraction patterns of the starting material FAPbBr3 obtained by two different preparation methods described in the present invention are shown. X-axis: 2θ (°); y-axis: intensity (arbitrary units); upper part: FAPbBr3 from solution according to Example 1; lower part: FAPbBr3 from dry grinding according to Example 2.

[0121] Figure 3 A TEM image of FAPbBr3 LC synthesized according to the present invention is shown, demonstrating the cubic nature of the crystal structure.

[0122] Figure 4 TEM images of FAPbBr3 LC synthesized according to the present invention are shown.

[0123] Figure 5 The Cs synthesized according to the present invention is shown 0.85 FA 0.15 TEM image of PbBr3 LC.

[0124] Figure 6 The Cs synthesized according to the present invention is shown 0.5 FA 0.5 TEM image of PbBr3 LC.

[0125] Figure 7 X-ray diffraction patterns of different precipitated LCs according to the invention are shown. X-axis: 2θ (°); y-axis: intensity (arbitrary units); upper part: CsPbBr3, middle part: Cs 0.5 FA 0.5 PbBr3; bottom: FAPbBr3. DETAILED DESCRIPTION

[0126] In a first aspect, the present invention relates to a method for producing luminescent crystals, in particular luminescent crystals from such quantum dots. More particularly, the present invention relates to a method for producing luminescent crystals of 3-500 nm in size, preferably 3-100 nm in size, selected from compounds of formula (I)

[0127] [M 1 A 1 ] a M2 b X c (I)

[0128] in

[0129] A 1 represents one or more organic cations, preferably selected from the group consisting of formamidinium, ammonium, guanidinium, protonated thiourea, imidazolium, pyridinium, pyrrolidinium,

[0130] M 1 represents one or more alkaline metals, preferably selected from Cs, Rb, K, Na, Li,

[0131] M 2 Indicates one or more different from M 1 The metal is preferably selected from Ge, Sn, Pb, Sb, and Bi,

[0132] X represents one or more anions selected from halides, pseudohalides and sulfides, preferably chloride, bromide, iodide, cyanide, thiocyanate, isothiocyanate and sulfide, particularly preferably one or more halides selected from Cl, Br and I,

[0133] a means 1-4,

[0134] b means 1-2,

[0135] c means 3-9;

[0136] The method comprises the steps of: (a) providing a solid material as defined below; and (b) dispersing the material in the presence of a liquid as defined below.

[0137] This aspect of the invention will be explained in further detail below.

[0138] As is well known, LC / QDs are environmentally sensitive materials. First, they tend to aggregate species that induce non-radiative recombination pathways, resulting in reduced luminescence quantum yield. Therefore, measures must be taken to stabilize LC / QDs once synthesized. The methods described herein meet this requirement by disclosing an improved manufacturing method to provide LC / QDs in the form of a stable suspension ("ink").

[0139] The methods described herein can be considered a "top-down" approach, as the materials are first conventionally synthesized, then reduced in size and stabilized to obtain LC / QDs. This approach is in contrast to the approach known and described in Protesescu and Aygüler (discussed above), which is a "bottom-up" approach. The methods of the present invention are further illustrated, but not limited to, the experiments provided below.

[0140] The methods described herein provide LC / QDs with excellent properties. First, small FWHM values ​​(width of the emission peak; for example, 26 nm for emission at 522 nm) were observed. Second, high luminescence quantum yields were observed (>80% for emission at about 530 nm). These quantum yields are high compared to the 5-15% reported in Aygüler (cited above). Therefore, the LC / QDs provided by the methods of the present invention are suitable for a large number of applications in electronic and optical devices. In addition, the LC / QDs provided by the methods of the present invention are also suitable for coating (non-electronic / non-optical) articles, such as decorative coatings.

[0141] Compared with known manufacturing methods, the method of the present invention is superior. First, it is more robust and can be easily scaled up. Second, it requires less starting materials and produces fewer by-products. Third, no solvent exchange to a low boiling point solvent (e.g., toluene) is required after the LC / QD synthesis, because the synthesis can be carried out directly in a low boiling point solvent. Fourth, a narrow size distribution of the resulting product is observed. Therefore, the manufacturing cost is greatly reduced, making LC / QDs useful for a large number of applications.

[0142] Luminescent crystals / quantum dots of formula (I): The method of the present invention provides LC / QDs having an average size of 3-500 nm, in particular 3-100 nm. The LC / QDs additionally have a narrow size distribution, as shown by the low FWHM value of the emission peak.

[0143] In one embodiment, the present invention relates to LC / QDs of formula (I), wherein a=1, b=1, c=3.

[0144] As can be seen from formula (I) above, the compounds subject to the present invention are heterogeneous materials because they include two types of cations, namely organic and metallic. 1 When it is an organic cation, the cation M 2 (and M 1 , if present) is a metal cation. According to the present invention, the organic cation A 1 In the compound of formula (I), the metal cation M 1 May or may not exist (A 1 ≠0;M 1 =0 or M 1 ≠0). Such hybrid materials, especially in the form of perovskite nanoparticles, have beneficial properties. A wide range of organic cations A 1The hybrid material (I) can be obtained according to the preparation method of the present invention. Suitable organic cations can be selected from carboxamidinium cations (IV-1), ammonium cations (IV-2), guanidinium cations (IV-3), protonated thiourea cations (IV-4), imidazolium cations (IV-5), pyridinium cations (IV-6), pyrrolidinium cations (IV-7),

[0145]

[0146] wherein the substituents R independently of one another represent hydrogen, or C 1-4 Alkyl, or phenyl, or benzyl and in case R is attached to carbon, it furthermore independently of one another represents a halide or a pseudohalide.

[0147] For (IV-1), R 2 preferably represents hydrogen; and R 1 Preferably represents methyl or hydrogen or halide or pseudohalide. Preferred cations are selected from acetamidine, formamidinium (FA). FA is the preferred cation.

[0148] For (IV-2), R preferably represents hydrogen and methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, phenyl, benzyl. Preferred cations are selected from benzyl ammonium, isobutyl ammonium, n-butyl ammonium, tert-butyl ammonium, diethyl ammonium, dimethyl ammonium, ethyl ammonium, methyl ammonium (MA), phenethyl ammonium, isopropyl ammonium, n-propyl ammonium. MA is a preferred cation.

[0149] For (IV-3), R 2 Preferably it represents hydrogen, resulting in the parent compound, the guanidinium cation.

[0150] For (IV-4), R 2 Preferably it represents hydrogen, resulting in the parent compound, protonating the thiourea cation.

[0151] For (IV-5), R 2 Preferably it represents methyl or hydrogen. Imidazolium is the preferred cation.

[0152] For (IV-6), R 2 Preferably represents methyl or hydrogen. Pyridinium is the preferred cation.

[0153] For (IV-7), R 2 Preferably represents methyl or hydrogen. Pyrrolidinium is the preferred cation.

[0154] It is understood that according to the present invention A 1 The presence of is mandatory. The compounds of formula (I) according to the invention are therefore referred to as organoperovskites.

[0155] M 1The amount of M can vary within a wide range. In one embodiment, the present invention relates to LC / QDs of formula (I), wherein M 1 In this embodiment, the present invention relates to a compound of formula (I-2)

[0156] A 1 a M 2 b X c (I-2)

[0157] wherein the substituents are defined herein. In this specification, such compounds of formula (I-2) are 1 Known as pure organic perovskite.

[0158] In a further embodiment, the invention relates to LC / QDs of formula (I), wherein when based on M 1 +A 1 Calculation time M 1 There is up to 90 mol%. In this embodiment, M 1 and A 1 Statistical distribution and compounds of formula (I-3)

[0159] [M 1 a` A 1 a`` ] a M 2 b X c (I-3)

[0160] in

[0161] a`+a``=1 and a` / (a`+a``)<0.9 and a`>0, and

[0162] wherein the remaining substituents are as defined herein. In this specification, such a compound of formula (I-3) is 1 The existence of is called inorganic-organic perovskite.

[0163] In one embodiment, the present invention relates to LC / QDs of formula (I), wherein M 1 =Cs.

[0164] In one embodiment, the present invention relates to LC / QDs of formula (I), wherein A 1 =FA.

[0165] In one embodiment, the present invention relates to LC / QDs of formula (I), wherein M 2 =Pb.

[0166] In one embodiment, the present invention relates to LC / QDs of formula (I), wherein X is a combination of at least two elements selected from Cl, Br, I.

[0167] In one embodiment, the present invention relates to LC / QD of formula (I), selected from FA1Pb1X3, in particular FAPbBr3, FAPbBr2I. This embodiment also includes a mixture of corresponding moles of FABr and PbBr2 or a mixture of FAI and PbBr2.

[0168] In another embodiment, the present invention relates to LC / QDs of formula (I), further comprising a doped material, i.e., wherein a portion of M 1 Replaced by other alkaline metals, or part of M 2 replaced by other transition metals or rare earth elements, or part of X is replaced by other halides, or part of A is replaced by 1 replaced by other cations as defined herein. The dopants (ie replacing ions) are generally present in an amount less than 1% relative to the ions they replace.

[0169] In a further embodiment the invention relates to LC / QD of formula (I-2) selected from A 1 SnX3, A 1 3Bi2X9,A 1 GeX3.

[0170] The compounds of formula (I) include stoichiometric and non-stoichiometric compounds. When a, b and c represent natural numbers (i.e. positive integers), the compounds of formula (I) are stoichiometric; when a, b and c represent rational numbers excluding natural numbers, they are non-stoichiometric.

[0171] In a further embodiment, the present invention relates to LC / QDs of formula (I), wherein a portion of X is replaced by one or more anions selected from cyanide, thiocyanate, isothiocyanate and sulfide.

[0172] A 1 a M 2 b X 1 c` X 2 c` ` (I-1),

[0173] in

[0174] A 1 、M 2 , a, b are identified above;

[0175] X1 represents one or more anions selected from the group consisting of halides, as identified above;

[0176] X 2 Indicates that it is different from X 1 an anion selected from a pseudohalide or sulfide, as identified above;

[0177] c`+c`` represents the natural number from 3 to 9 and c` / c``>0.9. Since the sulfide ion is 2-, it is counted twice when calculating c` and c``.

[0178] Exemplary embodiments of formula (I-1) include FAPbCl 2.9 CN 0.1 ,FASnBr2(SCN)1,FA3Bi2BR 8.8 (NCS) 0.2 , and FAPbBr 0.43 I 2.43 S 0.07 .

[0179] Step (a): The suitable solid material provided in step (a) has an average particle size of at least 100 nm, and a polydisperse size distribution of typically 50 nm to 100 μm, more typically 100 nm to 50 μm. The particle size of the solid material is determined by SEM, TEM, BET or centrifugal sedimentation.

[0180] Furthermore, the solid material has a chemical composition corresponding to the chemical composition of the desired LC / QD. Thus, the solid material has a molar (A 1 +M 1 ), b mole M 2 and c moles of X in stoichiometric composition.

[0181] This material can be provided to the process of the invention by different routes as outlined below (a1), (a2), (a3). The material can be provided to step (b) continuously or discontinuously by known methods. The material can be provided to step (b) as a solid material or in the form of a suspension.

[0182] Wet synthesis method (a1): The production of solid materials according to formula (I) is known per se. The most common methods include wet synthesis methods, such as precipitation from solvent-based or aqueous phases. The material can be provided to step (b) continuously or discontinuously by known methods.

[0183] Dry synthesis method by grinding (a2): Another route for making a solid material according to formula (I) involves dry grinding of precursor materials. In this embodiment, the solid material is two or more compounds having formula aA 1 1X1 and M2 b X (c-a) A mixture of dry precursors of wherein the substituents are defined above. For example, FAPbBr3, FA4PbBr6 can be obtained by corresponding molar mixtures of the precursors FABr and PbBr2 or FAPbBr2I, which can be obtained by corresponding mixtures of the precursors FAI and PbBr2. The dry crystalline material according to formula (I) is then obtained in a dry grinding process, for example, using a pestle and mortar or a process comprising stirring grinding balls. The process can be regarded as a solid-state reaction caused by grinding.

[0184] This approach can be considered "top-down": solid starting materials obtainable by dry grinding exhibit a polydisperse size distribution with an average particle size of >500 nm, typically between 1-50 microns (measured by SEM or centrifugal sedimentation), while synthetic luminescent crystals exhibit a very narrow size distribution with an average size of 3-500 nm. By following the methods described herein, the average particle size and polydispersity of the starting material are reduced to obtain a narrow size distribution and a particle size of 3-500 nm.

[0185] In situ formation (a3): Another alternative to the solid material according to formula (I) comprises in situ formation, for example a solid state reaction during dispersion. In this embodiment, the solid material is two or more compounds of formula aA 1 1X1 and M 2 b X (c-a) A mixture of dried precursors of wherein the substituents are defined above. For example, FAPbBr3, FA4PbBr6 can be obtained by a corresponding molar mixture of the precursors FABr and PbBr2 or FAPbBr2I, which can be obtained by a corresponding mixture of the precursors FAI and PbBr2. The crystalline material according to formula (I) is then formed during the dispersion process (i.e. in situ) by the reaction of the two precursors of the solid material.

[0186] The above-mentioned precursors can be obtained by known methods, such as wet synthesis, dry synthesis. Those skilled in the art can select suitable precursors to obtain luminescent crystals of formula (I). Similarly, this approach can also be considered as "top-down" because the precursors used are larger than the LC / QDs obtained.

[0187] In one embodiment, the average particle size of the solid material is at least 100 nm (determined by BET, SEM, TEM or centrifugal sedimentation), preferably 100 nm to 100 μm, more preferably 500 nm to 50 μm.

[0188] In an advantageous embodiment, the solid material consists of a single composition having the same stoichiometry as the final LC / QD of formula (I).

[0189] Step (b): Without being bound by theory, it is believed that a number of effects occur simultaneously or sequentially when the starting materials are dispersed in the liquid phase.

[0190] First, the solid material is evenly distributed in the liquid phase.

[0191] Next, the solid material is contacted with a surfactant. It is believed that the material is thereby coated and stabilized in the liquid phase.

[0192] Third, the particle size of the solid material is reduced. Without being bound by theory, it is believed that the monodisperse particle size distribution is achieved through two mechanisms: (1) mechanical crushing / fragmentation of particles larger than the final LC / QD size, and (2) Ostwald ripening and sintering of particles smaller than the final LC / QD size.

[0193] In a specific embodiment, the average particle size of the solid starting material is at least 1.5 times (preferably at least 2 times, most preferably at least 5 times) higher than the average particle size of the corresponding synthesized LC / QDs.

[0194] Liquid: As outlined above, step (b) is carried out in a liquid phase. Suitable liquids may be selected from (i) a liquid surfactant, (ii) a combination of a (liquid or solid) surfactant and a solvent, (iii) a combination of a (liquid or solid) surfactant, a solvent and a (liquid or solid) prepolymer or polymer and (iv) a combination of a (liquid or solid) surfactant and a liquid prepolymer.

[0195] In embodiment (i), the liquid phase consists of (or consists essentially of) a liquid surfactant. This embodiment is advantageous because it is a single system in which no solvent is used.

[0196] In embodiment (ii), the liquid phase consists of (or consists essentially of) a combination of a (liquid or solid) surfactant and one or more solvents. This embodiment is advantageous because it allows the use of solid surfactants.

[0197] In embodiment (iii), the liquid phase consists of (or consists essentially of) a combination of (liquid or solid) surfactant, one or more solvents and (liquid or solid) prepolymer or polymer. This embodiment is advantageous because it provides a composition that can be directly used to manufacture a component / intermediate as defined below.

[0198] In embodiment (iv), the liquid phase consists of (or consists essentially of) a liquid prepolymer. This embodiment is advantageous because it provides a composition which is solvent-free and can be used directly for the manufacture of a component / intermediate as defined below.

[0199] Solvent: The term solvent is as defined above. For the avoidance of doubt, the term solvent includes neither surfactants nor prepolymers.

[0200] Advantageously, the solvent is selected from hydrocarbons (including linear, branched and cyclic hydrocarbons), aromatic hydrocarbons, ethers (including glycol-ethers), esters, alcohols, ketones. Preferably, the solvent is selected from C 5-8 Cycloalkanes, straight and branched C 5-24 Alkanes which are unsubstituted or substituted with phenyl or naphthyl. Most preferably, the solvent is selected from linear C 5-15 Alkanes, toluene and cyclohexane.

[0201] In another embodiment, the solvent exhibits a boiling point below 140°C, preferably below 120°C. As a beneficial aspect of the method of the present invention, LC / QDs can now be obtained at much lower temperatures than previous methods such as Protesescu (discussed above, using a synthesis method of 140-200°C).

[0202] Prepolymer: The term prepolymer is defined above. Advantageously, the prepolymer is selected from acrylates, carbonates, sulfones, epoxies, vinyl compounds, polyurethanes, imides, esters, furans, melamines, styrenes, and silicones. Preferably, the prepolymer is selected from acrylates, polyurethanes, styrenes, epoxies. Particularly preferably, the prepolymer is selected from acrylates, and epoxies.

[0203] The acrylate prepolymer preferably comprises or consists of units of formula (III)

[0204] in:

[0205] R 9 Indicates H or CH3,

[0206] R 10 Indicates cyclic, straight or branched chain C 1-25 Alkyl, or cyclic\straight or branched C 2-25 Alkenyl, or C 6-26 Aryl, each optionally with one or more cyclic, linear or branched C 1-20 Alkyl, phenyl or phenoxy substituted,

[0207] n represents 0 or 1, and

[0208] X represents a spacer group derived from an alkoxylate containing 1 to 40 carbon atoms and 1 to 10 oxygen atoms.

[0209] X preferably represents a spacer group of formula (IIIa),

[0210] in:

[0211] x represents 1-10, preferably 1, 2, 3, or 4.

[0212] y represents 0, 1, 2, 3 or 4, preferably 2.

[0213] Thus, the compounds of formula (III) include acrylate prepolymers of formula (III-1) and (III-2), wherein R 9 is H, and a methacrylate prepolymer of formula (III-3) and (III-4), wherein R 9 It is a methyl group and is also collectively referred to as a (meth)acrylate prepolymer.

[0214] Furthermore, the compounds of formula (III) also include simple (meth)acrylate prepolymers in which n is 0 and X is absent (formulae (III-1) and (III-3) and alkoxylated (meth)acrylate prepolymers (formulae (III-2) and (III-4)).

[0215]

[0216] R represents an aliphatic group (saturated or unsaturated group) selected from cyclic, straight chain or straight chain branched molecules, or an aromatic group.

[0217] The acrylate prepolymer comprises monomers and partially reacted oligomers of formula (III).

[0218] R 10 Preferably, it represents a cyclic, linear or branched C 1-25 Cyclic alkyl groups include monocyclic and polycyclic groups and also include optionally substituted groups, which contain 1-4 1 to 6 substituents of the alkyl group. 10 Particularly preferably it represents methyl, ethyl, propyl, butyl, octyl, lauryl, cetyl, stearyl, 2-ethylhexyl, isooctyl, isodecyl, cyclohexyl, trimethyl-cyclohexyl, isobornyl, dicyclopentenyl.

[0219] R 10 More preferably, it represents a cyclic, linear or branched C 2-25 Alkenyl. 10 Particularly preferred are allyl and oleyl.

[0220] R 10 More preferably, C 6-26 Aryl, optionally with one or more cyclic, straight-chain or branched C 1-20 Aryl includes monocyclic and polycyclic aromatic groups, which may be optionally substituted by 1-4 substituents selected from C 1-4 Alkyl, phenyl and phenoxy. 10Particularly preferably it represents phenyl, benzyl, 2-naphthyl, 1-naphthyl, 9-fluorenyl.

[0221] Specific examples of the acrylate prepolymer of formula (III-1) include isobornyl acrylate and dicyclopentadienyl-acrylate (CAS 33791-58-1).

[0222] Specific examples of the acrylate prepolymers of formula (III-2) and (III-4) include: poly(ethylene glycol) phenyl ether acrylate (specifically 2-phenoxyethyl acrylate), o-phenylphenoxyethyl acrylate, polyethylene glycol o-phenylphenyl ether acrylate (CAS 72009-86-0), poly(ethylene glycol) ethyl ether methacrylate, di(ethylene glycol) ethyl ether acrylate, poly(ethylene oxide) nonylphenyl ether acrylate, poly(propylene glycol) 4-nonylphenyl ether acrylate, ethylene glycol dicyclopentenyl ether acrylate, ethylene glycol dicyclopentenyl ether methacrylate.

[0223] Due to R 10 According to the definition of , the (meth)acrylate prepolymer of formula (III) is monofunctional.

[0224] In another embodiment, the (meth)acrylate prepolymer is a multifunctional (meth)acrylate prepolymer. Such multifunctional (meth)acrylate prepolymers are obtainable when (meth)acrylic acid reacts with a polyol, thereby obtaining di-, tri-, tetra-, penta- and hexafunctional (meth)acrylate prepolymers. Suitable polyols for forming multifunctional (meth)acrylate prepolymers include aliphatic or aromatic C 1-30 polyols, optionally with one or more C 1-4 Alkoxy substituted, wherein the number of alkoxy groups is preferably ≤ 10, more preferably ≤ 5. Examples of polyols include diols, hexanediol, decanediol, bisphenol, fluorene-9-bisphenol, ethoxylated bisphenols containing 2-6, e.g. 4, ethoxy groups and ethoxylated fluorene-9-bisphenol containing 2-6, e.g. 4, ethoxy groups.

[0225] Specific examples of the difunctional (meth)acrylate prepolymer include 1,10-decanediol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol dimethacrylate, tricyclodecane dimethanol diacrylate, bisphenol A ethoxylate diacrylate (including CAS64401-02-1), bisphenol A ethoxylate dimethacrylate, modified fluorene-9-bisphenol diacrylate, modified fluorine-9-bisphenol dimethacrylate, and 1,3-butanediol dimethacrylate.

[0226] Specific examples of the trifunctional (meth)acrylate prepolymer include ethoxylated trimethylolpropane triacrylate (CAS 28961-43-5), trimethylolpropane triacrylate (CAS 15625-89-5), trimethylolpropane trimethacrylate (CAS 3290-92-4).

[0227] Specific examples of the tetrafunctional (meth)acrylate prepolymer include di(trimethylolpropane) tetraacrylate (CAS 94108-97-1), pentaerythritol tetraacrylate (CAS 4986-89-4).

[0228] Specific examples of the hexafunctional (meth)acrylate prepolymer include dipentaerythritol hexaacrylate (CAS 29570-58-9).

[0229] In the above discussion, mono- or polyfunctional (meth)acrylate prepolymers are particularly preferred, provided that:

[0230] R 10 Represents cyclic C 5-25 Alkyl, or

[0231] R 10 Represents cyclic C 5-25 Alkenyl, or

[0232] R 10 represents a substituted aryl group.

[0233] Among the mono- or polyfunctional (meth)acrylate prepolymers discussed above, very particular preference is given to compounds in which R 10 It represents isobornyl; dicyclopentenyl; bisphenol or fluorene-9-bisphenol.

[0234] Polymer: The term polymer is defined above. Advantageously, the polymer is selected from acrylate polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, polyurethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers and silicone polymers and cycloolefin copolymers.

[0235] The term acrylate polymer relates to a polymer comprising or consisting of the above-mentioned repeating units.

[0236] Acrylate polymers include homopolymers and copolymers. Acrylate copolymers preferably contain 50-100 wt.% of repeating units according to formula (III), particularly preferably 90-100 wt.%. Acrylate homopolymers contain one or more, preferably one, repeating unit of formula (III).

[0237] Surfactant: Various surfactants can be used in the context of the present invention. Suitable surfactants can be determined in routine experiments; their selection depends mainly on the nature of the polymer and solid materials used in the next step. The surfactant can be selected from the following classes: nonionic surfactants, cationic surfactants, zwitterionic surfactants and anionic surfactants.

[0238] In one embodiment, the surfactant is selected from anionic, cationic, nonionic and zwitterionic surfactants having one or more chemical moieties selected from alkyl ethers having formula (II)

[0239] RO-(C2H4O) m (C3H6O) n - (II), where

[0240] m and n are independently 0-10, but m+n>2, and

[0241] R stands for C 1-5 -alkyl.

[0242] It is known in the art to combine two or more surfactants to improve beneficial properties; such surfactant combinations are also subject to the present invention.

[0243] In another embodiment, the surfactant comprises a mixture of a zwitterionic surfactant and a nonionic surfactant, preferably a saturated or unsaturated fatty amine.

[0244] Nonionic surfactants include: maleic acid polymers such as poly(maleic anhydride-alt-1-octadecene), polyamines, alkyl amines (e.g. N-alkyl-1,3-propylene diamine, N-alkyl dipropylene triamine, N-alkyl tripropylene tetraamine, N-alkyl polypropylene-polyamine), poly(ethylene imine), polyesters, alkyl esters (e.g. cetyl palmitate), alkyl polyglycol ethers (e.g. fatty alcohol polyglycol ethers having 3-25 ethoxy units (EO), such as Dehypon E124 and oxo alcohol polyglycol ethers), mixed alkyl / aryl polyglycol ethers, alkyl polyglucosides (APGs), fatty alcohols such as stearyl alcohol (e.g. Lorol C18™), N-acyl amides (e.g. N-oleoyl-γ-aminobutyric acid).

[0245] Nonionic surfactants also include polymeric ethoxylate and / or propoxylate (EO / PO) adduct surfactants, such as fatty alcohol alkoxylates, alcohol EO / PO adducts (including fatty alcohol EO / PO adducts, oxo alcohol EO / PO adducts), EO / PO block copolymers, ethylenediamine oxide-propylene oxide (EO / PO) block copolymers, end-capped (fatty) alcohol EO adducts and EO / PO adducts (e.g. butyl end-capped), carboxylic acid esters, in particular EO / PO adducts and sorbitan esters (e.g. from SPAN).

[0246] Nonionic surfactants also include alkoxy-silanes and their hydrolysis products.

[0247] Nonionic surfactants also include alkyl phosphines, alkyl phosphine oxides (eg trioctylphosphine oxide -TOPO) and alkyl mercaptans.

[0248] Nonionic surfactants also include alkyl esters of fatty acids (eg cetyl palmitate, lauric acid, capric acid).

[0249] One class of preferred nonionic surfactants are the alkyl imines and alkyl amines, such as dioctylamine, oleylamine, octadecylamine, hexadecylamine.

[0250] Cationic surfactants include: alkyl ammonium halides such as oleyl ammonium bromide, alkyl trimethyl ammonium halides such as cetyl trimethyl ammonium bromide, dialkyl dimethyl ammonium halides such as distearyl dimethyl ammonium chloride, trialkyl methyl ammonium halides such as trioctyl methyl ammonium chloride, diquaternary polydimethylsiloxane.

[0251] Zwitterionic surfactants (also called amphoteric surfactants) are a known class of compounds. They consist of a cationic portion, preferably an amine salt, a quaternary ammonium group, a sulfonium or phosphonium group and an anionic portion, preferably a carboxylate, sulfonate, sulfite, sulfate, phosphinate, phosphonate, phosphite or phosphate group. Zwitterionic surfactants most preferably contain a quaternary ammonium as the cationic portion and a carboxylate, sulfonate or phosphonate as the anionic portion. Examples of zwitterionic surfactants include: betaines, such as caprylic acid glycinate, cocoamidopropyl betaine and disodium cocoamphodiacetate; 3-(N,N-dimethylalkylammonium) propane sulfonate, alkyl phosphate ammonium zwitterions.

[0252] A specific group of zwitterionic surfactants includes:

[0253] An ammonium carboxylate according to formula (V-1),

[0254] An ammonium derivative according to formula (V-2),

[0255] Phosphocholine according to formula (V-3),

[0256] 1-ammonium-2-propanol derivative of formula (V-4),

[0257] Aminoalkylammonium carboxylate of formula (V-5),

[0258] An aminoalkylammonium derivative of formula (V-6), and

[0259] 1-(Aminoalkyl-ammonium)-2-hydroxy-propyl derivatives of formula (V-7).

[0260] An ammonium carboxylate according to formula (V-1),

[0261] in:

[0262] R 5 is H or methyl,

[0263] V is 1-8, and

[0264] R 6 is a non-polar tail selected from substituted or unsubstituted hydrocarbons.

[0265] R 6 It is preferably selected from alkyl, alkoxy-alkyl, aryl-alkyl, aryloxy-alkyl, and alkenyl.

[0266] R 6 It is particularly preferred to be selected from a linear or branched alkyl group, more preferably a linear or branched C 8-30 Alkyl, most preferably C 10-20 alkyl.

[0267] v preferably represents an integer of 1-4.

[0268] A specific subgroup of ammonium carboxylates according to (V-1) includes glycinates (wherein R 5 is H and v is 1), dimethylammonium betaine (where R 5 is CH3 and v is 1), and ammonium propionate (where R 5 is H and v is 2).

[0269] An ammonium derivative according to formula (V-2),

[0270] in:

[0271] R 5 , R 6 and v is defined in formula (V-1), and

[0272] FG represents a negatively charged functional group.

[0273] FG is preferably selected from sulfonate (terminal group – SO3 - ), sulfite (terminal O-SO2- ), sulfate (terminal -O-SO3 - ), phosphonate (terminal group – P(OR 7 )O2 - ), phosphinate (terminal group – PR 7 O2 - ), phosphate (terminal -OP(OH)O2 - ) and phosphite (terminal -OP(H)O2 - ).

[0274] R 7 It is preferably selected from alkyl, alkoxy-alkyl, aryl-alkyl-, aryloxy-alkyl-, and alkenyl.

[0275] R 7 It is particularly preferred to be selected from a linear or branched alkyl group, more preferably a linear or branched C 8-30 Alkyl, most preferably C 10-20 alkyl.

[0276] A preferred subgroup is the ammonium sulfonate according to formula (V-2.1),

[0277] in:

[0278] R 5 , R 6 and v are as defined in formula (V-2).

[0279] A specific subgroup of ammonium sulfonates according to formula (V-2.1) includes sulfobetaines (wherein R 5 is CH3).

[0280] A further preferred subgroup is ammonium sulfite according to formula (V-2.2),

[0281] in:

[0282] R 5 , R 6 and v are defined as in formula (V-2).

[0283] A specific subgroup of ammonium sulfates according to formula (V-2.2) includes sulfite betaines, wherein R 5 For CH3.

[0284] A further preferred subgroup is ammonium sulfate according to formula (V-2.3),

[0285] in:

[0286] R 5 , R 6 and v are as defined in formula (V-2).

[0287] A specific subgroup of ammonium sulfates of formula (V-2.3) includes sulfate betaines, wherein R 5 =CH3.

[0288] A further preferred subgroup is the ammonium phosphonates according to formula (V-2.4),

[0289] in:

[0290] R 5 ,R 6 , R 7 and v is defined in formula (V-2), and

[0291] A specific subgroup of ammonium phosphonates according to formula (V-2.4) includes phosphonobetaines, wherein R 5 For CH3.

[0292] A further preferred subgroup is the ammonium phosphinate according to formula (V-2.5),

[0293] in:

[0294] R 5 , R 6 , R 7 And v is defined in formula (V-2).

[0295] A specific subgroup of ammonium phosphinates according to formula (V-2.5) includes phosphinate betaines, wherein R 5 =CH3.

[0296] A further preferred subgroup is ammonium phosphate according to formula (V-2.6),

[0297] in:

[0298] R 5 , R 6 and v are as defined in formula (V-2).

[0299] A specific subgroup of ammonium phosphates according to formula (V-2.6) includes phosphobetaines, wherein R 5 =CH3.

[0300] A further preferred subgroup is ammonium phosphite according to formula (V-2.7),

[0301] in:

[0302] R 5 , R 6 and v are as defined in formula (V-2).

[0303] A specific subgroup of ammonium phosphites according to formula (V-2.7) includes phosphite betaines, wherein R 5 =CH3.

[0304] A phosphorylcholine derivative according to formula (V-3),

[0305] in:

[0306] v is 1-8, preferably 1-4, particularly preferably 2,

[0307] R 5 is defined in formula (V-1),

[0308] R 6 is hydrogen or methyl, and

[0309] R8 is a non-polar tail selected from substituted or unsubstituted hydrocarbons.

[0310] R8 is preferably selected from alkyl, alkoxy-alkyl, aryl-alkyl-, aryloxy-alkyl-, and alkenyl.

[0311] R8 is particularly preferably selected from a linear or branched alkyl group, more preferably a linear or branched C 8-30 Alkyl, most preferably C 10-20 alkyl.

[0312] A specific subgroup of phosphorylcholines according to formula (V-3) includes phosphite betaines, wherein R 5 and R 6 is CH3. A specific example is miltefosine.

[0313] 1-ammonium-2-propanol-derivatives of formula (V-4),

[0314] in:

[0315] R 5 and R 6 is defined in formula (V-1), and

[0316] FG represents a negatively charged functional group.

[0317] FG is preferably selected from sulfonate (terminal group – SO3 - ), sulfite (terminal O-SO2 - ), sulfate (terminal -O-SO3 - ), phosphonate (terminal group – P(OR 7 )O2 - ), phosphinate (terminal group – PR 7 O2 - ), phosphate (terminal -OP(OH)O2 -) and phosphite (terminal -OP(H)O2 - ), where R 7 As defined above.

[0318] FG particularly preferably represents a sulfonate group. A specific subgroup of compounds of formula (V-4) includes hydroxysulfobetaines in which R 5 and R 6 is CH3 and FG is –SO3 - .

[0319] Aminoalkylammonium carboxylate of formula (V-5),

[0320] in:

[0321] R 5 , R 6 and v is defined in formula (V-1), and

[0322] W is 2-5, preferably 2.

[0323] An aminoalkylammonium derivative of formula (V-6),

[0324] in:

[0325] R 5 , R 6 and v is defined in formula (V-1),

[0326] W is 2-5, preferably 2, and

[0327] FG represents a negatively charged functional group.

[0328] FG is preferably selected from sulfonate (terminal group – SO3 – ), sulfite (terminal O-SO2 - ), sulfate (terminal -O-SO3 - ), phosphonate (terminal group – P(OR 7 )O2 - ), phosphinate (terminal group – PR 7 O2 - ), phosphate (terminal -OP(OH)O2 - ) and phosphite (terminal -OP(H)O2 - ), where R 7 As defined above.

[0329] FG particularly preferably represents a sulfonate group. A specific subgroup of the aminoalkylammonium sulfonates includes the aminoalkylsulfobetaines in which R 5 is CH3 and FG is –SO3 - .

[0330] 1-(Aminoalkyl-ammonium)-2-hydroxy-propyl derivatives according to formula (V-7)

[0331] in:

[0332] R 5 and R 6 is defined in formula (V-1), and

[0333] FG represents a negatively charged functional group.

[0334] FG particularly preferably represents a sulfonate group. A specific subgroup of the aminoalkylhydroxysulfonates includes the aminoalkylhydroxysulfobetaines in which R 5 is CH3 and FG is –SO3 - .

[0335] Imidazolinium derived amphoteric surfactants: This group includes amphoacetates (mono- or diacetates) and amphopropionates.

[0336] Anionic surfactants include sulfates, sulfonates, phosphates, and carboxylates. Specific examples include alkyl ether phosphates, ammonium lauryl sulfate, alkali lauryl sulfate, and related alkyl-ether sulfates such as polyethylene glycol monolauryl ether sulfate alkali.

[0337] One preferred class of anionic surfactants are carboxylates from the class of fatty acids such as oleic acid, stearic acid, palmitic acid.

[0338] In a preferred embodiment, the surfactant is selected from the following list: SP13300, SP20000, SP24000SC, SP41000, SP540, BYK9077, Hypermer KD1-SO-(AP), Span65, Span80, Span85, methoxy-ethoxy-ethoxy-acetic acid, oleylamine, oleic acid, stearic acid, poly(maleic anhydride-alt-1-octadecene), oleyl ammonium bromide, 3-(N,N-dimethyl-octadecyl-ammonium) propane sulfonate, miltefosine and TOPO.

[0339] In a further embodiment, the surfactant is selected from anionic, cationic, nonionic and zwitterionic surfactants comprising a non-polar end group selected from an alkyl or alkyl-ether chain having 4-30, preferably 6-24, most preferably 8-20 carbon atoms.

[0340] In a further embodiment, the anionic surfactant is selected from monocarboxylic acids comprising a polyether tail according to formula (II),

[0341] R(OC n H 2n ) qOCH2C(O)OH (II-1)

[0342] Where R is C 1-5 -alkyl, q is an integer from 0 to 5 and n is an integer from 1 to 3. Five particularly preferred compounds of this type are:

[0343]

[0344] wherein q is 0-4. This corresponds to compounds of formula (II) in which R = methyl, n = 2 and q is an integer from 0 to 4. Particularly preferred compounds of this type are compounds of (II-1b),

[0345]

[0346] Dispersion process: Suitable dispersion processes are known in the art and include dispersion methods involving grinding balls, dispersion processes by ultrasound, dispersion by high shear mixing and high pressure dispersion.

[0347] Ball milling: In a preferred embodiment, the dispersion method is ball milling, preferably by using an agitator ball mill. In a preferred embodiment, the ball size is less than 5 mm, preferably less than 500 microns. In a further embodiment, the dispersion method is ball milling with a ball size between 10–1000 μm, preferably 20–500 μm. In a further embodiment, the dispersion method is ball milling using a specific power input / suspension weight of at least 10 W / kg, preferably 100 W / kg, most preferably 1000 W / kg. In a further embodiment, the suspension temperature during the dispersion process is less than 140°C, preferably less than 120°C, most preferably less than 70°C. It was surprisingly found that the solid material defined above can be converted into LC / QDs having excellent optical properties (high quantum yield, small FWHM) by using agitator grinding balls, providing LC / QDs having excellent properties and at low reaction temperatures. This is considered to be a significant advantage over known methods.

[0348] Ultrasonic waves: In another preferred embodiment, the dispersion method comprises ultrasonic waves, preferably using an ultrasonic horn. Particularly preferably, the dispersion method is ultrasonic waves with 10-100kHz, preferably 20-30kHz. In another embodiment, the dispersion method is ultrasonic waves with a specific power input / suspension weight of at least 10W / kg, preferably 100W / kg, and most preferably 1000W / kg. In a further embodiment, the suspension temperature during the ultrasonic process is slightly below 140°C, preferably below 120°C, and most preferably below 70°C. Surprisingly, it has been found that the solid material defined above can be converted into LC / QDs having excellent optical properties (high quantum yield, small FWHM) by using ultrasonic waves, providing LC / QDs having excellent properties and at low reaction temperatures. This is considered to be a significant advantage over known methods.

[0349] High shear mixing: In a further preferred embodiment, the dispersion method comprises high shear mixing, for example obtained using a stator / rotor configuration. Particularly preferably, the dispersion method is high shear mixing with a shear rate of 20'000-100'000 1 / s, preferably 50'000-100'000 1 / s. In a further embodiment, the suspension temperature during high shear mixing is below 140° C., preferably below 120° C., most preferably below 70° C. This is considered to be a significant advantage over known methods.

[0350] High-pressure dispersion: In a further preferred embodiment, the dispersion process comprises high-pressure dispersion, also known as high-pressure homogenization, in which impact, shear forces and cavities act as driving forces for the dispersion. Particularly preferably, the dispersion process is a high-pressure dispersion with a pressure of 150-400 MPa, preferably 200-400 MPa. In a further embodiment, the suspension temperature during the high-pressure dispersion is below 140° C., preferably below 120° C., most preferably below 70° C. This is considered to be a significant advantage over known methods.

[0351] The concentration of the solid material provided in step (b) may vary within a wide range, but is typically 100 ppm or more. In a further embodiment of the process of the present invention, the weight ratio of solid material: liquid material (solvent + surfactant + prepolymer (if present) + polymer (if present)) is 0.0001-0.5, preferably 0.0001-0.3, most preferably 0.0001-0.1.

[0352] The concentration of the surfactant provided in step (b) may vary within a wide range, depending on its nature. In a further embodiment of the process of the invention, the weight ratio of surfactant:solid material is 100-0.01, preferably 50-0.015, most preferably 3-0.02.

[0353] Step (c): In further embodiments, the as-synthesized LC / QDs may be subjected to post-processing, for example as outlined in steps (c-1), (c-2), (c-3), and (c-4) below.

[0354] In one embodiment of such post-processing, the halide atom X of the synthesized LC / QD can be completely or partially replaced with other halide atoms by anion exchange. In particular, alkali halides, such as CsI, RbI, NaI, KI, LiI, and lead halides, such as PbI2, and organic halides such as FAI can be used for anion exchange (c-1). This allows fine tuning of the emission peak.

[0355] In another embodiment of such post-processing, two or more types of luminescent crystals of formula (I) are mixed. By mixing different types of luminescent crystals, for example by combining two suspensions containing such LCs, the emission peak of the composition is adjusted. (c-4)

[0356] In another embodiment, the composition of the present invention can be purified by diafiltration of the synthesized composition with excess surfactant. (c-2)

[0357] In other embodiments, the LC / QD solid content of the composition of the present invention can be increased by synthesizing the composition by diafiltration or solvent evaporation. (c-3)

[0358] In a second aspect, the present invention relates to a composition in the form of a suspension (also referred to as an "ink"), and uses thereof. This aspect of the invention will be described in detail below.

[0359] Therefore, the present invention also provides a composition in the form of a suspension, which comprises (i) a luminescent crystal of formula (I) as described herein; (ii) a surfactant as described herein, but excluding octylammonium bromide, oleic acid; and (iii) optionally a solvent as described herein; and (iv) optionally a polymer or prepolymer as described herein. Such a composition is novel and can be obtained by the method of the present invention as described in the first aspect of the present invention.

[0360] In one embodiment, the invention provides a suspension wherein the quantum yield thereof is >20%, preferably >50%, most preferably >70%.

[0361] In a further embodiment, the invention provides a suspension wherein the FWHM of the LC / QDs for visible emission is <50 nm, preferably <40 nm, most preferably <30 nm.

[0362] In further embodiments, the invention provides a suspension wherein the FWHM of the LC / QDs having an emission peak between 480-550 nm or between 600-680 nm is <50 nm, preferably <40 nm, most preferably <30 nm.

[0363] In a further embodiment, the invention provides a suspension wherein the FWHM of the LC / QDs having an emission peak between 480-550 nm is <40 nm, preferably <30 nm, most preferably <20 nm.

[0364] The amounts of components (i), (ii), (iii) and (iv) in the inks of the invention may vary within wide limits and depend inter alia on their intended use and the nature of the surfactant. Typically, the amount of LC / QD is 100 ppm or more.

[0365] In one embodiment, the weight ratio of luminescent crystal (i): liquid material (ii) + (iii) + (iv) is 0.0001-0.5, preferably 0.0001-0.3, most preferably 0.0001-0.1.

[0366] In a further embodiment, the weight ratio of surfactant (ii):luminescent crystal (i) is 100-0.01, preferably 50-0.015, most preferably 3-0.02.

[0367] In a further embodiment, the polymer or prepolymer concentration is 0.1-30 wt%, preferably 0.5-20 wt%, most preferably 1-10 wt% of the total composition.

[0368] As outlined above, components (i) and (ii) are mandatory, whereas components (iii) and (iv) are optional. The present invention therefore relates to an ink comprising (i.e. comprising or consisting of):

[0369] Components (i) and (ii), whereby (ii) is a liquid, and (iii) and (iv) are absent;

[0370] Components (i), (ii), (iii), without (iv);

[0371] Components (i), (ii), (iv) without (iii) (solvent-free ink);

[0372] Components (i), (ii), (iii) and (iv)

[0373] Component (i), liquid (ii), without (iii), without (iv) (concentrate).

[0374] In a further embodiment, the composition comprises components (i), (ii), (iii) and (iv), wherein component (ii) comprises an aromatic hydrocarbon, preferably toluene or a cycloalkane, preferably cyclohexane and component (iv) comprises a cycloolefin copolymer.

[0375] In a further embodiment, the composition comprises components (i), (ii), (iii) and (iv), wherein component (ii) comprises linear alkanes and / or aromatic hydrocarbons and / or cycloalkanes and component (iv) comprises styrene copolymers and / or styrene block copolymers.

[0376] In a preferred embodiment, the composition comprises a luminescent crystal of formula (I) selected from FA1Pb1X3. In this embodiment, the surfactant (ii) preferably comprises a zwitterionic surfactant, and / or the polymer / prepolymer (iv) is selected from acrylates.

[0377] Solvent-free ink: The present invention provides a composition as described herein in the form of a suspension, comprising components (i), (ii) and (iv), but which is free or substantially free of solvent (iii). In this embodiment, the weight ratio of LC / QD (i): liquid material (prepolymer (iv) + surfactant (ii)) is preferably 0.0001-0.2, preferably 0.0001-0.1, most preferably 0.0001-0.01. Such a composition may be referred to as a solvent-free ink and is particularly suitable for supplying it to manufacturers of components or equipment discussed below.

[0378] Prepolymers particularly suitable for solvent-free inks include acrylates, epoxies, polyurethanes, silicones, styrenes. Again, the term prepolymer includes monomers and oligomers thereof. Preferred solvent-free inks include acrylates.

[0379] An ink is considered solvent-free when it contains less than 10 wt % solvent, preferably less than 1 wt % solvent.

[0380] In further embodiments, the solvent-free ink further comprises a polymerization initiator, such as a free radical photoinitiator or a temperature sensitive free radical initiator.

[0381] Concentrate: The present invention provides a composition as described herein in the form of a suspension, which is free or substantially free of solvent (iii), which is free or substantially free of prepolymer (iv) and wherein surfactant (ii) is a liquid surfactant. In this embodiment, the weight ratio of surfactant (ii): LC / QD (i) is preferably 100-0.01, preferably 50-0.015, most preferably 3-0.02.

[0382] The inks described herein find many applications, they are particularly useful for converting blue light into white light, particularly using light emitting diodes (LEDs).

[0383] In a third aspect, the present invention relates to a solid polymer composition and uses thereof. The term solid polymer composition refers to an organic or inorganic polymer matrix comprising the LC / QDs described herein. This aspect of the invention will be described in detail below.

[0384] In one embodiment, the present invention provides a solid polymer composition comprising (i) LC / QDs as described herein, (ii) a surfactant as described herein, and (iii) a hardened / cured polymer, preferably selected from organic polymers.

[0385] In other embodiments, the organic polymer is preferably selected from acrylate polymers, carbonate polymers, sulfone polymers, epoxy polymers, vinyl polymers, polyurethane polymers, imide polymers, ester polymers, furan polymers, melamine polymers, styrene polymers and silicone polymers. Therefore, the polymer preferably comprises repeating units of the prepolymer described herein. In addition, the polymer can be linear or cross-linked.

[0386] In other embodiments, the organic polymer is preferably selected from acrylate polymers, epoxy polymers, polyurethane polymers, styrene polymers, silicone polymers and cycloolefin copolymers. Therefore, the polymer preferably comprises repeating units of the prepolymer described herein. In addition, the polymer can be linear or cross-linked.

[0387] In one embodiment, the organic polymer comprises a styrene copolymer and / or a styrene block copolymer, preferably a block copolymer of styrene and isoprene and a block copolymer of styrene, ethylene and butylene.

[0388] The amount of LC / QD in the solid polymer composition of the present invention can vary over a wide range, but is typically 10 ppm or more. In one embodiment, the weight ratio of LC / QD: matrix (polymer + surfactant) in the solid polymer composition is 0.00001-0.2, preferably 0.00005-0.15, and most preferably 0.0001-0.1. In one embodiment, the solid polymer composition of the present invention is in the form of microparticles, and the microparticles preferably contain 1-10 wt% of the LC / QD described herein. In another embodiment, the solid polymer composition of the present invention is in the form of a film, and the film preferably contains 0.01-0.5 wt% of the LC / QD described herein.

[0389] In one embodiment, the weight ratio of surfactant:LC / QD in the solid polymer composition is 100-0.01, preferably 50-0.015, most preferably 3-0.02.

[0390] In other embodiments, the quantum yield of the solid polymer composition of the present invention is >20%, preferably >50%, most preferably >70%.

[0391] In other embodiments, the FWHMs of the solid polymer compositions of the present invention for visible emission are <50 nm, preferably <40 nm, most preferably <30 nm.

[0392] In a fourth aspect, the present invention relates to an assembly (also referred to as an intermediate) comprising a sheet-like substrate coated with one or more layers, wherein at least one of the layers is a functional layer, wherein the functional layer comprises a solid polymer composition as described herein. This aspect of the invention will be described in detail below.

[0393] In an advantageous embodiment, the functional layer converts blue light into white light.The present invention therefore provides the use of a solid polymer composition for converting blue light into white light, in particular using light-emitting diodes (LEDs) or in liquid crystal displays.

[0394] In a fifth aspect, the present invention relates to novel devices / articles comprising a solid polymer composition as described herein. This aspect of the invention will be described in detail below.

[0395] In one embodiment, the present invention provides a device selected from an electronic device and an optical device, wherein the device comprises a substrate and a functional layer as described herein (the fourth aspect of the present invention). Such a device can be selected from a display, a mobile device, a light emitting device, and a solar cell, in particular wherein the device is a liquid crystal display (LCD) or a quantum dot LED (QLED).

[0396] In one embodiment, the present invention provides an article comprising a substrate and a coating, particularly a decorative coating, comprising the LC / QDs of formula (I) described herein and a surfactant described herein.

[0397] In a sixth aspect, the present invention relates to a method for making a polymer composition as described herein. The method comprises steps known in the art, but by using the ink as described herein (second aspect) as one starting material or the only starting material.

[0398] In a seventh aspect, the present invention relates to a method of making a component / intermediate product as described herein. This aspect of the invention will be described in detail below.

[0399] The component / intermediate according to the invention can be obtained by a solution process. This is considered to be a significant advantage, since it enables all layers to be manufactured by a simple technology suitable for large areas and continuous processing. Therefore, the present invention also provides a method for manufacturing a component as described herein, comprising the steps of: (e) providing a substrate, and (f) depositing a solid polymer composition as described herein on said substrate, preferably by coating or printing an ink as described herein, followed by drying and / or curing.

[0400] In an eighth aspect, the present invention relates to a method for manufacturing the electronic device described herein. This aspect of the present invention will be described in detail below.

[0401] The manufacture of a device starting from the components described above is known per se, but has not yet been applied to the specific components of the present invention.

[0402] To further illustrate the present invention, the following examples are provided. These examples are not intended to limit the scope of the present invention. If not otherwise stated, all chemicals were purchased from Aldrich.

[0403] Example 1: Synthesis of a solid material obtained by precipitation (solid material from solution)

[0404] Step (a): Formamidinium lead tribromide (FAPbBr3) was synthesized by dissolving PbBr2 and FABr in a mixture of N,N-dimethylformamidinium (DMF, >99.8%, puriss., Sigma Aldrich):γ-butyrolactone (GBL, >99% Sigma Aldrich) in a 1:1 volume ratio. That is, 4mmol PbBr2 (1.468g, 98+% Alfa Aesar) and 4mmol FABr (0.500g, Dyesol) were dissolved in 4ml DMF / GBL at 25°C and under vigorous stirring. Orange FAPBBr3 crystals of about 1-5mm size were grown by heating the solution to 80°C for 24 hours. It was further filtered and dried in vacuum at room temperature for another 24 hours. The crystalline phase (cubic) and composition were confirmed by XRD ( Figure 2 , upper spectrum). This material does not show any luminescence.

[0405] Step (b): The dried FAPbBr3 microcrystals were crushed into powder using a pestle and mortar and added to oleylamine (80-90%, Acros) (FAPbBr3: oleylamine = 2:1) and toluene (>99.7%, Fluka). The final concentration of FAPbBr3 was 1 wt%. The mixture was then dispersed by ball milling using 50 micron-sized yttrium-stabilized zirconia beads under ambient conditions for 1 hour to produce an ink with green luminescence.

[0406] Analysis: The optical properties of the ink were measured in a 10 mm quartz cuvette (3 μl of ink diluted in 3 ml of toluene) using a fluorescence spectrophotometer equipped with an integrating sphere (Quantaurus Absolute PL Quantum Yield Measurement System C1134711, Hamamatsu). The photoluminescence quantum yield of the above ink was 83%, with the emission peak centered at 511 nm. The FWHM of the emission was determined to be 29 nm.

[0407] TEM analysis of ink ( Figure 3 ) shows the presence of cubic particles with a very narrow particle size distribution.

[0408] Conclusion: This example shows the effectiveness of the method of the present invention.

[0409] Example 2: Synthesis of solid material obtained by dry grinding

[0410] Step (a): Formamidinium lead tribromide (FAPbBr3) was synthesized by grinding PbBr2 and FABr. That is, 16 mmol PbBr2 (5.87 g, 98% ABCR) and 16 mmol FABr (2.00 g, Dyesol) were ground with yttrium-stabilized zirconia beads (5 mm in diameter) for 6 hours to obtain pure cubic FAPbBr3, which was confirmed by XRD ( Figure 2 , lower spectrum). This material does not show any luminescence. By centrifugal sedimentation method (LUMiSizer, LUM GmbH), 12 mg of powder was mixed with 10 ml of S20 viscosity oil standard (psl rheotek) and a 2 mm polyamide cuvette was used to obtain a hydrodynamic particle size distribution (volume weighted). Produce an average particle size (D50) of 7 microns and a size range (D10-D90) of 1-12 microns.

[0411] Step (b): Orange FAPbBr3 powder was added to oleic acid (90%, Sigma Aldrich), oleylamine (80-90, Acros) (FAPbBr3: oleic acid: oleylamine = 2:1:1) and cyclohexane (>99.5%, puriss, Sigma Aldrich). The final concentration of FAPbBr3 was 1 wt%. The mixture was then dispersed by ball milling using 200 micron-sized yttrium-stabilized zirconia beads under ambient conditions for 1 hour to produce an ink with green luminescence.

[0412] Analysis: The luminescent properties of the ink were recorded as described in Example 1. The photoluminescent quantum yield (PLQY) of the above ink was 97% with an emission peak centered at 522 nm (=peak position, PP). The FWHM of the emission was determined to be 42 nm.

[0413] Film formation: The green emission ink was then mixed with a 10% cyclic olefin copolymer (COC, TOPAS Advanced Polymers) solution in toluene, coated on a glass substrate and dried at 60° C. for 15 minutes. After drying, the optical properties of the film were measured using a fluorescence spectrophotometer equipped with an integrating sphere (Quantaurus Absolute PL Quantum Yield Measurement System C1134711, Hamamatsu).

[0414] Analysis: The photoluminescence quantum yield of the film was 90%, with the emission peak centered at 528 nm. The FWHM was determined to be 30 nm. The resulting film was subjected to a degradation test at elevated temperature for 2 hours in a drying oven (80°C, ambient humidity). The photoluminescence quantum yield of the film after degradation was 79%, with the emission peak centered at 527 nm. The FWHM was determined to be 30 nm.

[0415] Conclusion: This example shows the effectiveness of the process of the invention from dry-milled solid material and the preparation and degradation stability of the solid polymer composition of the invention.

[0416] Example 3-8: Synthesis using alternative surfactants and solvents

[0417] Step (a): Formamidinium lead tribromide (FAPbBr3) was synthesized as described in Example 2.

[0418] Step (b): The following further experiments were all performed by ball milling using similar process parameters (LC / QD:total surfactant ratio = 2:1, milling bead size = 200 microns, milling time = 60 min, LC / QD concentration in ink = 1%, filtered through a 0.45 μm PTFE syringe filter for optical characterization, which was the same as in Example 1):

[0419]

[0420] Conclusion: These examples show the effectiveness of the method of the present invention using different surfactant classes and solvents.

[0421] Example 9: Synthesis of a solid material consisting of a mixture of two different precursors

[0422] Step (a): Commercial FABr (Dyesol) and PbBr2 (98%, ABCR) powders were mixed in an equimolar ratio, resulting in a pure stoichiometric composition of FAPbBr3.

[0423] Step (b): The salt mixture was added to oleylamine (80-90%, Acros) and oleic acid (90%, Sigma Aldrich) (FAPbBr3: oleylamine: oleic acid = 2:1:1) and cyclohexane (>99.5%, puriss, Sigma Aldrich). The final concentration of FAPbBr3 was 1 wt%. The mixture was then dispersed by ball milling using 200 micron-sized yttrium-stabilized zirconia beads at ambient conditions for 60 minutes to produce an ink with green luminescence.

[0424] Analysis: The luminescent properties of the ink were recorded as described in Example 1. The photoluminescent quantum yield of the above ink was 48% with the emission peak centered at 503 nm. The FWHM of the emission was determined to be 37 nm.

[0425] Conclusion: This example shows the effectiveness of the method of the invention using in situ formation as described herein.

[0426] Example 10: Comparison of thermal stability of organic, inorganic and organic-inorganic LCs

[0427] Synthesis: The following materials were obtained by dry grinding as described in Example 2: CsPbBr3, Cs 0.85 FA 0.15 PbBr3, Cs 0.5 FA 0.5 PbBr3, Cs 0.15 FA 0.85 PbBr3. Luminescent inks and films were prepared similarly to the procedure described in Example 2.

[0428] Analysis: XRD revealed no peaks for CsBr, FABr or PbBr2 in the solid material (dry ground starting material), confirming the single phase formation of mixed cations in the lattice.

[0429] Centrifugal sedimentation (LUMiSizer, LUM GmbH) showed similar hydrodynamic size distributions for all materials with D10 between 0.8 and 2 microns, D50 between 1 and 12 microns and D90 between 4 and 35 microns.

[0430] From FAPbBr3( Figure 4 ), Cs 0.85 FA 0.15 PbBr3( Figure 5 ) and Cs 0.5 FA 0.5 PbBr3( Figure 6 ) showed LCs with sizes ranging from 5-50 nm.

[0431] Table 2 shows the optical properties of the inks and films initially obtained. Table 3 shows the properties of the films after degradation for 2 hours at 80°C and ambient humidity (ie about 5% relative humidity) and after degradation for 2 hours at 60°C and 90% relative humidity.

[0432] Table 2:

[0433]

[0434] *Due to the dilution effect of ink, the measurement results may be biased

[0435] Table 3:

[0436]

[0437] Conclusion: The data clearly show the high PLQY of both the ink and the film. For the film, this high PLQY is maintained even after stress testing under severe conditions.

[0438] Example 11: Synthesis of red emitting LC via solid material obtained by dry grinding method.

[0439] Step (a): Commercial formamidinium iodide (>99%, Dyesol) and PbI2 (98.5%, Alfa Aesar) were mixed in an equimolar ratio to obtain a pure stoichiometric composition of FAPbI3. The powder mixture was dry ground using 5 mm yttrium stabilized zirconia beads at ambient conditions for 400 minutes and then dried at 80°C.

[0440] Step (b): The salt mixture was added to oleylamine (80-90%, Acros Organics) and oleic acid (90%, Sigma Aldrich) in cyclohexane (≥99%, Sigma Aldrich) (CsPbBr3: oleylamine: oleic acid = 2:1:1). The final concentration of FAPbI3 was 1 wt%. The mixture was then dispersed by ball milling using yttrium stabilized zirconia beads with a size of 200 microns under ambient conditions for 60 minutes to produce an ink with red luminescence. Film samples were prepared similarly to the procedure in Example 2.

[0441] Analysis: The photoluminescence quantum yield of the above polymer film was 71%, with the emission peak centered at 758 nm. The FWHM of the emission was determined to be 89 nm.

[0442] Conclusion: The results clearly show that red-emitting LCs composed of FAPbI3 can be obtained using the method of the present invention.

[0443] Example 12: Synthesis of green emitting LC and transfer to a suspension containing prepolymer / polymer and its solid polymer composition.

[0444] Step (a): FAPbBr3 was obtained as described in Example 2.

[0445] Step (b): Orange FAPbBr3 powder was added to (lauryl dimethyl ammonium) acetate (>95%, SigmaAldrich), oleylamine (80-90%, Acros) (FAPbBr3: (dodecyl dimethyl ammonium) acetate: oleylamine = 1:0.1:0.3) and toluene (>99.7%, Fluka). The final concentration of FAPbBr3 was 1wt%. The mixture was then dispersed under ambient conditions for 1 hour using yttrium-stabilized zirconia beads with a size of 200 microns by ball milling to obtain an ink with green luminescence.

[0446] Analysis: The luminescent properties of the ink were recorded as described in Example 1. The photoluminescent quantum yield (PLQY) of the above ink was 88% with a luminescence peak centered at 528 nm (=peak position, PP). The FWHM of the emission was determined to be 24 nm.

[0447] Film formation: The green emitting ink was then mixed with different polymers / prepolymers. For acrylates, 1 wt% Irgacure 184 was mixed with the acrylate as an initiator. The toluene from the acrylate / ink mixture was passed through a vacuum (10 -2 mbar) was evaporated at room temperature and the mixture was coated between two glass substrates with a thickness of 100 μm and cured with UV (Hoenle UVAcube 100, Hg lamp with quartz filter, 1 minute). For cyclic olefin copolymer, polycarbonate (Makrolon OD2015) and polystyrene (Mw=35,000, Sigma Aldrich), films were obtained similarly to Example 2.

[0448] Analysis: Table 4 shows the optical properties of the films measured using a fluorescence spectrophotometer equipped with an integrating sphere (Quantaurus Absolute PL Quantum Yield Measurement System C1134711, Hamamatsu).

[0449] Table 4:

[0450]

[0451] *:Sartomer SR506D:Sartomer SR595 (95wt%:5wt%);

[0452] **:Makrolon OD2015

[0453] Conclusion: This example shows the effectiveness of the process of the present invention for preparing suspensions and solid polymer compositions using different polymers.

[0454] Example 13: Synthesis of suspension by ultrasound

[0455] Step (a): FAPbBr3 was obtained as described in Example 2.

[0456] Step (b): Orange FAPbBr3 powder was added to (lauryl-dimethylammonium) acetate (>95%, SigmaAldrich), oleylamine (80-90%, Acros) (FAPbBr3: (N,N-dimethyl-octadecylammonium) propane sulfonate: oleylamine = 3:0.1:0.2) and toluene (>99.7%, Fluka). 10 g of the mixture was then dispersed by ultrasound using a 50W ultrasonic generator at 50% amplitude and an ultrasonic horn with a diameter of 5 mm (Dr. Hilscher, UP50H). The processing time was 30 minutes and the temperature was 72°C. This procedure produced an ink with green luminescence.

[0457] Analysis: The luminescent properties of the ink were recorded as described in Example 1. The photoluminescent quantum yield (PLQY) of the above ink was 53% with the emission peak centered at 528 nm (=peak position, PP). The FWHM of the emission was determined to be 30 nm.

Claims

1. A composition in the form of a suspension comprising In a first embodiment, (i) luminescent crystals with a size of 3-100 nm, wherein the luminescent crystals are selected from compounds of formula (I) [M 1 A 1 ] a M 2 b X c (I), in: A 1 represents formamidinium, M 1 represents Cs, M 2 represents a metal selected from Ge, Sn and Pb, X represents one or more anions selected from chloride, bromide and iodide, a represents 1, b represents 1, c represents 3, and A 1 Existence and M 1 exists or does not exist; and (ii) a surfactant selected from nonionic, anionic and cationic surfactants; and (iii) an optional solvent selected from aliphatic hydrocarbons including linear, branched and cyclic hydrocarbons, aromatic hydrocarbons, ethers including glycol-ethers, esters, alcohols, ketones; (iv) a polymer and / or a prepolymer, wherein the polymer is selected from an acrylate polymer and the prepolymer is selected from an acrylate, wherein the acrylate comprises or consists of a monofunctional unit of formula (III) R 9 Indicates H or CH 3 , R 10 Represents cyclic C 5-25 Alkyl, cyclic C 5-25 Alkenyl, or C 6-26 Aryl, wherein the C 6-26 The aryl group is selected from phenyl, benzyl, 2-naphthyl, 1-naphthyl, 9-fluorenyl, wherein the cyclic C 5-25 Alkyl is unsubstituted or has 1-6 C 1-4 substituted with an alkyl substituent, and the C 6-26 Aryl is unsubstituted or substituted with 1-4 C 1-4 Alkyl substituents are substituted, n represents 0 or 1, and X represents a spacer group of formula (IIIa), x represents 1-10, y represents 0, 1, 2, 3 or 4; Or in a second embodiment, (i) luminescent crystals with a size of 3-100 nm, wherein the luminescent crystals are selected from compounds of formula (I) [M 1 A 1 ] a M 2 b X c (I) where: A 1 represents formamidinium, M 1 represents Cs, M 2 represents a metal selected from Ge, Sn and Pb, X represents one or more anions selected from chloride, bromide and iodide, a represents 1, b represents 1, c represents 3, and A 1 Existence and M 1 exists or does not exist; and (ii) a surfactant selected from zwitterionic surfactants; and (iii) an optional solvent selected from aliphatic hydrocarbons including linear, branched and cyclic hydrocarbons, aromatic hydrocarbons, ethers including glycol-ethers, esters, alcohols, ketones; (iv) a polymer and / or a prepolymer, wherein the polymer is selected from acrylate polymers; and the prepolymer is selected from acrylates, and epoxy resins.

2. The composition according to claim 1, wherein ● The luminescent crystal (i) is selected from FA 1 Pb 1 X 3 , wherein FA represents formamidinium; and / or ● the composition is free of solvent (iii); and / or ● The acrylic ester is selected from isobornyl acrylate and dicyclopentenyl acrylate.

3. The composition according to claim 1 or 2, wherein ● The weight ratio of luminescent crystals (i):((ii)+(iii)+(iv)) is 0.0001-0.5; and / or ● The weight ratio of surfactant (ii):luminescent crystal (i) is 100-0.01; and / or ● wherein the polymer or prepolymer concentration is 0.1-30 wt % of the total composition.

4. The composition according to claim 1 or 2, wherein the surfactant comprises a non-polar terminal group selected from an alkyl or alkyl ether chain having 4 to 30 carbon atoms.

5. The composition according to claim 1 or 2, ● the composition is free of solvent (iii), and ● The weight ratio of luminescent crystal (i): (prepolymer (iv) + surfactant (ii)) is 0.0001-0.

2.

6. The composition according to claim 1 or 2, ● wherein the surfactant (ii) is a liquid surfactant and the composition is free of solvent (iii) and prepolymer (iv), and ●Wherein the weight ratio of surfactant (ii):luminescent crystal (i) is 100–0.

01.

7. The composition according to claim 1 or 2, wherein ● The luminescent crystal (i) is selected from FA 1 Pb 1 X 3 , where FA represents formamidinium; ● In a second embodiment the surfactant (ii) is selected from zwitterionic surfactants; and ● The prepolymer is selected from acrylates, and the polymer is selected from acrylate polymers.

8. The composition in the form of a suspension according to claim 1, which is the first embodiment.

9. A solid polymer composition comprising: In a first embodiment, (i) luminescent crystals of formula (I) defined in claim 1 or 2 with a size of 3-100 nm, and (ii) a surfactant selected from the group consisting of nonionic, anionic and cationic surfactants; (iv) a hardened / cured polymer selected from the group consisting of acrylate polymers of formula (III) as defined in claim 1; or In a second embodiment, (i) luminescent crystals of formula (I) defined in claim 1 or 2 with a size of 3-100 nm, and (ii) a surfactant selected from zwitterionic surfactants; (iv) a hardened / cured polymer selected from acrylate polymers, epoxy polymers.

10. The solid polymer composition according to claim 9, wherein ● The luminescent crystal (i) is selected from FA 1 Pb 1 X 3 , where FA represents formamidinium; ● In a second embodiment the surfactant (ii) is selected from zwitterionic surfactants; and ● The polymer (iv) is selected from acrylate polymers.

11. The solid polymer composition according to claim 9 or 10, in: ● The weight ratio of luminescent crystal: (polymer + surfactant) is 0.00001-0.2; and / or ●The weight ratio of surfactant:luminescent crystal is 100-0.

01.

12. The solid polymer composition according to claim 9, which is the first embodiment.

13. Assembly comprising a sheet-like substrate coated with one or more layers, wherein at least one of the layers is a functional layer, wherein the functional layer comprises a solid polymer composition according to any one of claims 9 to 12.

14. A device selected from electronic devices and optical devices, wherein The device comprises a substrate and a functional layer; and The functional layer comprises a solid polymer composition according to any one of claims 9-12.

15. The device of claim 14, selected from a display, a mobile device, a light emitting device and a solar cell.

16. Products, wherein The article comprises a substrate and a coating, The coating comprises a solid polymer composition according to any one of claims 9-12.